Sero-prevalence and risk factors associated with occurrence of anti-Brucella antibodies among slaughterhouse workers in Uganda - Bugeza, James Katamba; Alinaitwe, Lordrick; Kristina, Roesel; Mugizi, Denis Rwabiita; Kivali, Velma; Kankya, Clovice; Ignacio, Moriyon; Elizabeth, AnneJessieCook (PLOS Neglected Tropical Diseases, 2024)
Brucellosis is a febrile zoonosis occurring among high-risk groups such as abattoir workers and is a public health priority in Uganda. Whereas bacteriological isolation is conclusive, and some molecular methods have been found useful for diagnosis of brucellosis, they are technically complex and may delay commencement of treatment. Therefore, clinicians from resource poor settings rely on clinical examination and serology for diagnosis of human brucellosis. However, brucellosis lacks pathognomonic signs, and clinically resembles other endemic febrile illnesses which complicates diagnosis. Poor quality Brucella antigens, serological tests not validated for human use, and lack of consensus on the tests of choice complicate diagnosis of brucellosis. Previously, many studies employed a variety of tests to estimate sero-prevalence of brucellosis in high-risk groups leading in some cases to over estimation of the disease in Uganda. Here we applied the RBT and BrucellaCapt tests in a serial testing scheme to detect contacts, short and long evolution cases of brucellosis and report a sero-prevalence ranging from 7.3% to 9.0% among slaughter house workers in Uganda. Brucella seropositivity was associated with the region where participants worked, the slaughter of cattle, small ruminants, and grazing animals as an activity outside the work of the slaughterhouse.